eTandem language learning and foreign language anxiety among colombian learners of german - El-Hariri, Yasmin (Colombian Applied Linguistics Journal, 2017)
Although eTandems, offering the opportunity of real life contact to speakers of one’s target language, are suggested as an anxiety-reducing, confidence-increasing approach to language learning (Appel & Gilabert, 2002), these effects have not been investigated empirically. The aim of this article is to explore the experiences and perceptions of 11 Colombian learners of German as a foreign language who participated in a German-Spanish eTandem project. Data were collected by means of interviews and focus groups, and evaluated using qualitative content analysis. Results support the anxiety-reducing and confidence-raising nature of eTandem Language Learning. eTandems show to have great potential to reduce the fear of using German in real life situations. These perceptions, however, are not in every case transferable into the language classroom.